Improving Food Safety Risk Assessment in Vietnam : Facilitating the Setting-up of a National Food Safety Risk Assessment Committee - World Bank (Washington, DC, 2022)
Vietnam’s agricultural sector plays an important role in the global agri-food value chain. As the sector having the highest trade surplus in one of the most open economies in the world, Vietnam’s agricultural sector was affected by Coronavirus (COVID-19) in two main ways. Firstly, raw materials and immediate input supplies for the sector were disrupted due to the early outbreak in Asian countries, especially China, which supply most agricultural inputs such as fertilizers and plant protection products. Secondly and compounding this trend, demand has dropped significantly due to mobility restrictions and reduced economic activity within the country and its most important markets, such as the US and Europe. The objective of this study was to enhance Vietnam’s trade and competitiveness, focusing on strengthening private sector participation in global value-chains and food safety awareness and compliance. This report is structured as follows. The first chapter presents the context, objectives and approach for the study. The second chapter highlights the key issues, challenges and gaps in Vietnam’s food safety risk assessment. The third chapter presents some of the key lessons and experiences in food safety risk management from some countries within the region and more advanced economies, as a basis to inform Vietnam’s national food safety risk assessment framework. Chapter four makes recommendations on how to strengthen Vietnam’s National food safety risk assessment committee.